Indigenous Exile from Cosmopolitan Nar-rative: : Fight/Resistance of Indigenous Self against Historic Trauma in Bangladesh - Saha, Aroop (Dia-noesis: A Journal of Philosophy, 2025)
This article aims to discover a new strategy for the indigenous subjects of Bangladesh to encounter the memories of the indigenous exile and trauma in the 21st century. As the indigenous people of Bangladesh are struggling to overcome the bitter experiences of the historical exile and the multifaceted trauma received during the British Raj, East Pakistan, and Bangladesh, they are becoming the double-victims of history and reality. This complex situation constrains the indigenous psyche to restrain the indigenous self and society from composing the indigenous story. The limit surfaces as the inability to represent the indigenous self before the national narrative. This inability restricts the indigenous meaning-making process, making constructing an indigenous identity difficult. Consequently, the indigenous self and society cannot formulate the indigenous perspective and voice beyond its sphere. This situation excludes the indigenous self from the national narrative.